Advowsons and Private Patronage. (September 2019) - Sutton, Teresa
Abstract : This article focuses on the role of private patronage within the Church of England. Private patrons own advowsons. These property rights can no longer be traded but may still be bequeathed or transferred without value. When there is a vacancy in a benefice, a patron has the right to nominate a new incumbent in accordance with the Patronage (Benefices) Measure 1986. This article uses contemporary and historical records to define private patronage and analyse the current role of the four broad categories of private patrons: private individuals, educational bodies, guilds and patronage societies. While acknowledging the benefits that patronage can bring, this article advocates substantive reform for the future including a sunset rule for private individual patronage. The article suggests that reform of the law of private patronage will make a positive contribution to other contemporary issues before the Church by promoting diversity in vocations, facilitating necessary pastoral reorganisation and adding to the dialogue about the future of the parish system.